Factors Influencing the Molecular Compositions and Distributions of Atmospheric Nitrogen‐Containing Compounds. Issue 7 (30th March 2022) - Jiang, Hongxing; Li, Jun; Tang, Jiao; Zhao, Shizhen; Chen, Yinjun; Tian, Chongguo; Zhang, Xiangyun; Jiang, Bin; Liao, Yuhong; Zhang, Gan
Abstract: Atmospheric nitrogen‐containing organic compounds (NOCs) are critical components of global nitrogen deposition and light‐absorption species. The sources and compositions of NOCs are complex and remain largely unknown. Here, NOCs in 55 ambient aerosol samples collected in Guangzhou, South China, were analyzed via ultrahigh‐resolution Fourier transform ion cyclotron resonance mass spectrometry in negative‐ion and positive‐ion electrospray ionization (ESI) modes. The molecular compositions of NOCs measured via ESI– and ESI+ exhibited considerable differences. NOCs detected in the negative mode were mainly composed of highly oxygenated organic nitrates (O/N = 6), whereas NOCs detected in the positive mode were mainly composed of reduced nitrogen‐containing compounds (e.g., amides and amino acids). CHN compounds potentially corresponding to amines and alkaloids showed low abundance in the detection modes. Non‐metric multidimensional scaling and individual compound correlation analyses showed that the molecular compositions of NOCs were mainly affected by anthropogenic activities and meteorological parameters. For example, anthropogenic activities such as biomass burning and secondary nitrogen‐chemistry processes led to the accumulation of aromatic and highly oxygenated NOCs during winter. During summer, higher OH radical concentrations and temperatures will result in more prevalent or persistent reduced aliphatic NOCs, particularly lipid‐like amines. Some variables (e.g., relative humidity) have distinct effects on the variation of different types of NOCs. More research is needed to reveal the influencing mechanisms. This study clarifies the molecular compositions of NOCs and the mechanisms by which various factors influence the molecular variations. The findings can guide the assessment of NOCs evolution and deposition. Plain Language Summary: Negative and positive electrospray ionization coupled with Fourier transform ion cyclotron resonance mass spectrometry (ESI‐FT‐ICR‐MS) was used to characterize the molecular composition of nitrogen‐containing organic compounds (NOCs) from aerosol samples in Guangzhou. It was determined that a large amount of various NOCs are present in the samples, with NOCs in highly oxidative and reduced states can be roughly identified by distinct ionization modes. By combining the ESI‐FT‐ICR‐MS results and statistical analysis, the factors that associated with the distribution of NOCs and how these factors worked were identified. Anthropogenic activities and meteorological parameters (e.g., temperature and oxidation levels) are the two important drivers that led to the variations of NOCs, resulting to inverse molecular patterns with different response to aromatic/highly unsaturated and saturated structures, respectively. This study provides a useful clue for studying NOCs in complex system, bridges the links between the filed observation and knowledge about sources and formation pathways of NOCs that derived from controlled laboratory studies. Key Points: Most of identified CHON− species had O/N ≥ 3 and showed higher O/C ratios than CHON+ species; CHN only constituted small fraction of nitrogen‐containing organic compounds (NOCs) Biomass burning and secondary inorganic‐nitrogen processes lead to the accumulation of aromatic and phenolic NOCs during winter Higher OH radical concentrations and temperatures result in more prevalent or persistent reduced aliphatic NOCs in summer